Impact cratering rate consistency test from ages of layered ejecta on Mars - Lagain, Anthony; Bouley, S.; Baratoux, D.; Costard, F.; Wieczorek, M. (2019)
© 2019 Elsevier Ltd Ages of geological units of planetary bodies are determined from impact crater counts on their surface. These ages are model-dependent, and several models largely used in the community assume a constant production function and a constant cratering rate over the last 3 Ga. We have mapped the population of small impact craters (>200 m in diameter) formed over a population of large impact craters (>5 km in diameter) with layered ejecta on Acidalia Planitia, Mars. We have deduced the age of each large impact crater under the assumption of a constant impact rate and constant production function. The impact rate inferred from this set of ages is, however, not constant and show a significant increasing during the last ~1 Ga compared to chronology models commonly used. We interpret this inconsistency as an evidence for temporal variations in the size-frequency distribution (SFD) of impactors in the main belt, consistent with recent studies argued for a late increasing of the large impactor flux on Earth and the Moon.